Effectiveness of Functional Mandibular Advancer in Patients with Class II Malocclusion: A Systematic Review and Meta-analysis - M. Dilip Kumar; Haritha Pottipalli Sathyanarayana; Vignesh Kailasam (Galenos Yayinevi, 2023)
Objective: We aimed to evaluate the effectiveness of functional mandibular advancer (FMA) in treating growing patients with Class II malocclusion. Methods: Electronic searches were conducted in MEDLINE (via PubMed), Cochrane Library, Web of Science, Scopus, Embase, and Lilacs from 1945 to 30th November 2021. Studies were selected based on the following inclusion criteria: human studies, Class II growing patient treated with FMA, untreated control group or a comparable group treated with another fixed functional appliance, pre- and post-treatment lateral cephalograms/magnetic resonance imaging/cone-beam computed tomography, randomized clinical trials, prospective studies, and retrospective studies. Data extraction of the included articles was independently performed independently by two authors. The risk of bias was assessed using the ROBINS-I tool. Meta-analysis was performed using the inverse generic model. Results: Seven articles met the criteria and were included in the systematic review and three articles were included in the meta-analysis. Three studies had at low risk of bias and four studies had a moderate risk of bias. All articles reported anterior positioning of the mandible along with an increase in mandibular length. The meta-analysis results indicated a negligible difference between FMA and other functional appliances for the parameters SNA [0.11, 95% confidence interval (CI) of -1.07 and 1.29] and ANB (-1.00, 95% CI of -1.34 and -0.65). The evidence was limited for soft tissue changes. Conclusion: Class II correction with FMA involved a combination of skeletal and dentoalveolar changes and was similar to other fixed functional appliances.